Preparation method of small-hole anti-pollution PTFE-ZrO2 composite membrane with low surface energy
By preparing low-surface energy PTFE-ZrO2 composite film, the pollution and flux problems of ceramic membrane in the fermentation broth system are solved, and efficient anti-pollution performance and stable penetration performance are achieved.
Patent Information
- Application Number
- CN202411163508.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Ceramic membranes are prone to bacterial adhesion, protein adsorption and small molecule fragments blocking pores in the fermentation broth system, resulting in membrane contamination and degradation of performance.
Using a low-surface energy PTFE-ZrO2 composite membrane, the membrane with specific surface energy is formed by mixing PTFE emulsion with ZrO2 dispersion to reduce microbial adhesion and protein adsorption, and the membrane's anti-pollution performance is improved through sintering process optimization. .
It effectively reduces membrane pollution, improves membrane flux in the fermentation broth, and achieves improvement of anti-pollution performance and stability of penetration performance.
Smart Images

Figure CN119455677A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic membranes, and particularly relates to a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy and a preparation method thereof. Background Art
[0002] The biological fermentation broth system is very complex, with multi-scale, multi-phase and multi-media characteristics. In addition to the target product, it also contains cell fragments, bacteria, proteins, polysaccharides, metabolites, pigments and salt ions. This complexity makes the ceramic membrane prone to problems such as bacterial adhesion, protein adsorption and small molecule fragments blocking the pores during the filtration process. Microbial contamination accounts for about 45% of membrane contamination in the fermentation broth system. During operation, the microorganisms in the fermentation broth will adhere to the membrane surface, deposit and multiply, and simultaneously secrete extracellular polymers (EPS), further enhancing their stable attachment to the membrane surface. This will lead to the formation of a dense biofilm, which will seriously affect the performance of the ceramic membrane.
[0003] Currently, an effective strategy to mitigate microbial contamination during membrane separation is to regulate the surface energy of the membrane to reduce the adhesion of bacteria. Surface energy plays a key role in determining the adhesion of microorganisms to the surface of the material. The regulation of the surface energy of ceramic membranes can be achieved by introducing low surface energy substances. The hydrophilic surface of the ceramic membrane has the characteristics of fouling resistance and can form a hydration layer to mitigate membrane fouling. However, during long-term operation, pollutants continue to accumulate on the surface and may interrupt the function of the hydration layer. The introduction of low surface energy organic materials can fundamentally change the surface energy of the ceramic membrane, allowing it to continue to resist the attachment of microorganisms during long-term operation and effectively prevent the formation of biofilms on the membrane surface. Among the many low surface energy materials, polytetrafluoroethylene (PTFE) is considered to be an ideal material for reducing the surface energy of ceramic membranes due to its excellent chemical stability and high temperature resistance.
[0004] The incorporation of PTFE particles into ZrO2 particles to prepare low surface energy ultrafiltration membranes involves an organic-inorganic mixing process and faces two key issues. One is the dispersibility of the membrane-making solution. Physical mixing of materials of different particle sizes and charges usually leads to particle agglomeration and inhomogeneity, which in turn leads to problems such as uneven membrane thickness and surface cracking. Another key issue lies in the sintering process of the membrane. Ceramic membranes usually require higher sintering temperatures, while the melting point of PTFE is relatively low, making the composite membrane unsuitable for sintering at high temperatures. Otherwise, the melting of PTFE particles will destroy the integrity and anti-fouling properties of the membrane surface. Therefore, it is necessary to develop a sintering process suitable for composite membranes.
[0005] In this study, we prepared a PTFE-ZrO2 composite membrane that can reduce membrane fouling and improve membrane flux in fermentation broth. The synergistic effect of the hydrophilicity of ZrO2 and the low surface energy of PTFE was used to enhance the anti-fouling performance of the membrane. We studied the dispersion effect and mechanism of dispersant and pH on ZrO2 dispersion and PTFE emulsion to optimize the stable dispersion conditions of PTFE-ZrO2 mixture. In addition, the preparation process of the membrane was optimized, and its permeability and anti-fouling properties in simulated and real fermentation broth clarification were studied. Summary of the invention
[0006] In order to reduce membrane pollution during clarification of fermentation broth and improve membrane flux in the fermentation broth, the present invention utilizes the synergistic effect of the hydrophilicity of ZrO2 and the low surface energy of PTFE to provide an anti-pollution PTFE-ZrO2 composite membrane with specific surface energy and a preparation method thereof, which has the characteristics of good anti-pollution performance, stable permeation and high flux.
[0007] The technical solution of the present invention is:
[0008] A method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy comprises the following steps:
[0009] Step 1, mixing PTFE emulsion and ZrO2 dispersion to obtain PTFE-ZrO2 dispersion;
[0010] Step 2, coating the ceramic membrane tube with a PTFE-ZrO2 dispersion by dip coating;
[0011] Step 3, drying and sintering to obtain the PTFE-ZrO2 composite membrane.
[0012] The solid content of the ZrO2 dispersion is 1-5%, the solid content of the PTFE emulsion is 40-70%, and the volume ratio of the PTFE emulsion to the ZrO2 dispersion is 1:9-1:1, and preferably 1:2-1:4.
[0013] The pH value of PTFE emulsion and ZrO2 dispersion is 9-13.
[0014] The PTFE emulsion and / or ZrO2 dispersion also contains a dispersant, which is selected from NH4PAA or AEO-3. When NH4PAA is used in the ZrO2 dispersion, and the mass ratio of NH4PAA to ZrO2 is 0.005-0.05, AEO-3 is used in the PTFE emulsion, and the mass ratio of AEO-3 to PTFE is 0.001-0.005.
[0015] The coating time of dip coating is 20-50s.
[0016] The sintering temperature in step 3 is 300°C-350°C, preferably 335-345°C.
[0017] The surface roughness Ra of the composite film is 20-30nm, and the surface energy is 25-35mJ·m -2 , the composite film thickness is 1-2μm.
[0018] Application of low surface energy small pore anti-fouling PTFE-ZrO2 composite membrane in fermentation broth filtration and clarification.
[0019] The clarification working conditions of the composite membrane are: a membrane surface flow rate of 0.5-5 m / s and a transmembrane pressure difference of 0.1-1 MPa.
[0020] Beneficial Effects
[0021] The present invention prepares a pollution-resistant PTFE-ZrO2 composite membrane with a specific surface energy by adding a polytetrafluoroethylene (PTFE) emulsion into a zirconium oxide (ZrO2) dispersion. This membrane can not only reduce the clogging and adsorption of proteins, but also reduce the adhesion of microorganisms by adjusting the surface energy, thereby alleviating membrane pollution in the fermentation liquid. At the same time, the composite membrane of the present invention realizes the synergistic optimization of the dual defense mechanism, improves the anti-pollution performance of the membrane, and has good prospects for application in fermentation liquid clarification. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 :Characterization of ZrO2 dispersion and PTFE emulsion. (a) Zeta potential of ZrO2 dispersion and PTFE emulsion; (b) Particle size distribution of ZrO2 dispersion; (c) Particle size distribution of PTFE emulsion.
[0023] Figure 2 : Schematic diagram of the dispersion mechanism of PTFE and ZrO2 particles.
[0024] Figure 3 : Effect of dispersant concentration on ZrO2 dispersion and PTFE emulsion at pH 11. (a) Zeta potential of ZrO2 dispersion; (b) particle size distribution of ZrO2 dispersion; (c) Zeta potential of PTFE emulsion; (d) particle size distribution of PTFE emulsion. Figure 4 :Effect of different volume ratios on the Zeta potential of PTFE-ZrO2 mixed dispersions.
[0025] Figure 5 :Effect of sintering temperature on membrane surface morphology and permeability (V PTFE / V ZrO2=1:3). (a) Surface morphology of the membrane at 320°C; (b) Surface morphology of the membrane at 340°C; (c) Surface morphology of the membrane at 360°C; (d) Pure water permeability; (e) Water dynamic contact angle; (f) Diiodomethane dynamic contact angle (the initial static contact angle is shown in the picture).
[0026] Figure 6 : Microstructure characterization. (a) Surface morphology of the composite film; (b) Distribution of Zr on the film surface; (c) Distribution of F on the film surface; (d) AFM images of the base film and the composite film; (e) EDS line scan analysis (the red line indicates the line scan trajectory).
[0027] Figure 7 :The effect of PTFE doping amount on surface energy and permeability. (a) Contact angle and surface free energy; (b) Pure water permeability of base film, ZrO2 film and composite film.
[0028] Figure 8 : Filtration test in simulated ethanol fermentation broth. (a) Flux of base membrane, ZrO2 and composite membrane in simulated ethanol fermentation broth; (b) Flux recovery rate (FRR) of base membrane, ZrO2 and composite membrane after pure water and chemical cleaning.
[0029] Fig. 9 : Cyclic antifouling test of membrane in simulated fermentation broth.
[0030] Fig.10 : Filtration test in ethanol fermentation broth. (a) Flux of base membrane, ZrO2 and composite membrane in actual ethanol fermentation broth; (b) Flux recovery rate (FRR) of base membrane, ZrO2 and composite membrane after pure water and chemical cleaning. DETAILED DESCRIPTION
[0031] Preparation of PTFE-ZrO2 dispersion and composite membrane
[0032] First, the ZrO2 dispersion (solid content 2%) and the PTFE emulsion (solid content 60%) were ultrasonically treated for 30 minutes. Subsequently, the pH values of the ZrO2 dispersion and the PTFE emulsion were adjusted with nitric acid or ammonia water, respectively. Then, the corresponding dispersant was added to each dispersion: fatty alcohol polyoxyethylene ether (AEO-3) was used to disperse PTFE particles, while ammonium polyacrylate (NH4PAA) was used to disperse ZrO2 particles. The two were mixed and stirred continuously for 30 minutes, and a constant pH value was maintained throughout the process. After stirring, the PTFE-ZrO2 dispersion was obtained by ultrasonic treatment for 5 minutes, and then the composite membrane was prepared by dip coating. The base membrane used was an alumina microfiltration membrane with an average pore size of 100nm, and the coating time was 30s.
[0033] Due to the presence of PTFE emulsion and dispersant, the dispersion exhibits a certain degree of viscosity, so no additional thickener is added during the preparation process. The resulting composite membrane is named according to the volume ratio of PTFE and ZrO2 dispersion, for example, P1Z2 means that the volume ratio of PTFE and ZrO2 is 1:2.
[0034] Subsequently, the membrane tube was dried at 25 °C for 12 hours and then transferred to an oven and dried at 70 °C and 110 °C for 12 hours, respectively. Finally, the membrane tube was placed in a muffle furnace and sintered at a specific temperature, and the sintering time was controlled to be 2 hours. Different composite membranes were prepared by controlling the solid content of the PTFE-ZrO2 mixed dispersion, adjusting the volume ratio of PTFE to ZrO2, and changing the coating time. In order to compare the performance of the composite membrane, a batch of ZrO2 membranes were prepared using ZrO2 dispersion under the same conditions.
[0035] Membrane characterization
[0036] The wettability of the membrane was characterized by measuring the contact angle (OCA-25, Dataphysics, Germany). The test drop volume was 3 μL, and three points were measured for each membrane tube to obtain the average value as the result. The surface free energy of the membrane was calculated by calculating the static water contact angle (WCA) and diiodomethane contact angle (DCA) of the membrane surface using the Owens-Wendt-Kaelble equation:
[0037]
[0038] where γ is the total surface free energy, γ D is the dispersion surface free energy, γ P is the polar surface free energy, θ is the static contact angle, and L and S represent the liquid and solid phases, respectively.
[0039] Simulated fermentation broth filtration performance test
[0040] In order to study the anti-fouling performance of the prepared composite membrane, a 5 g·L -1 yeast, 8wt% ethanol, 10g·L -1 of glucose and 5 g·L -1 The simulated fermentation broth of sucrose was used for flux measurement in the simulated system.
[0041] In the cyclic antifouling test, a -1 Bovine serum albumin (BSA), 5 g L -1 Yeast, 8wt% ethanol, 10g·L -1 Glucose and 5g·L -1Simulated ethanol fermentation broth of sucrose to accurately simulate the substances produced in microbial metabolic activities. During the test, it was first tested with pure water for 60 minutes, and then filtered with simulated fermentation broth for 60 minutes. This process was repeated three times, and then rinsed with pure water for another 60 minutes. When cleaning the membrane tube, the membrane tube was rinsed with pure water for the first 30 minutes while keeping the permeate side closed. Subsequently, the permeate side was opened and rinsed with pure water for another 30 minutes. The pure water flux of the membrane was then measured to determine the pure water cleaning recovery rate. Next, the membrane was chemically cleaned for 1 hour using 1.0wt% NaOH and 1.0wt% NaClO solution, and then its pure water flux was tested. The entire process was repeated to obtain the flux recovery rate of different membranes after chemical cleaning.
[0042] Ethanol fermentation broth filtration performance test
[0043] The ethanol fermentation broth filtration experiment was conducted to evaluate the anti-fouling performance of different membranes in the actual fermentation environment. The ethanol fermentation broth was obtained from Shougang Langze Technology Co., Ltd. The solid content of the fermentation broth was measured to be 3.6wt% and the protein content was 6.40g·L -1 , determined using the Coomassie Brilliant Blue staining method.
[0044] Dispersibility of PTFE-ZrO2 mixed solution
[0045] In order to obtain a composite membrane with excellent performance and integrity, a well-dispersed PTFE-ZrO2 mixture is required. In solutions with different pH values, the surface charge of the nanoparticles will change, which in turn affects their dispersion properties. Figure 1 The results show that the isoelectric point of the ZrO2 dispersion is about 6.67, and it exhibits a uniform particle size distribution (about 60-70nm) under acidic and alkaline conditions. In contrast, the PTFE emulsion shows a negative Zeta potential in the pH range of 3-11, and the particle size remains at about 200nm and is evenly distributed. Since the initial pH value of the ZrO2 dispersion is about 3, and the pH value of the PTFE emulsion is about 8, the two have opposite charges, and direct mixing will cause particle aggregation due to mutual attraction. Adjusting the two dispersions to alkaline conditions above pH 9 will help the dispersion of the mixed solution because they both show a negative Zeta potential at this time.
[0046] In addition to the electrostatic effect under alkaline conditions, the dispersibility was further optimized by introducing dispersants to enhance the steric repulsion. Figure 2A schematic diagram of the dispersion mechanism of PTFE and ZrO2 particles under alkaline conditions is shown. NH4PAA, as an anionic polyelectrolyte, is easily adsorbed to the surface of ZrO2 particles through chemical adsorption and ionized under alkaline conditions to form negatively charged carboxyl groups, which enhances the electrostatic repulsion between ZrO2 particles. The dispersion of PTFE particles is attributed to the steric hindrance effect. The oxygen atoms in the ether bonds on the EO chain (green circles in the figure) can form hydrogen bonds with water molecules, thereby forming a stable and thick hydration layer on the outer surface of the PTFE particles. This hydration layer can effectively prevent other particles from approaching, thereby promoting the stability of the two particles in the suspension.
[0047] Optimizing the dispersant concentration can achieve the best dispersion stability of the dispersion. Figure 3 As shown in a, when NH4PAA is added at pH 11, the absolute value of the Zeta potential of the ZrO2 dispersion increases significantly, while the average particle size decreases. When the mass ratio of the added NH4PAA to ZrO2 is 0.01, the Zeta potential of the dispersion increases and the particle size distribution becomes narrower ( Figure 3 b). It was also found that the average particle size of ZrO2 particles at pH 11 was significantly smaller than that at pH 9, and the particle size distribution was narrower. Figure 3 The Zeta potential of the PTFE emulsion in c also showed an upward trend at pH 11 with the addition of AEO-3. The particle size distribution of PTFE particles at pH 11 was narrower and more concentrated than that at pH 9. When the mass ratio of AEO-3 was 0.0025 or 0.005, the average particle size was smaller ( Figure 3 Based on the above results, and considering that as little dispersant as possible should be added during the dispersion process, it is believed that under pH 11, when the mass ratio of NH4PAA to ZrO2 is 0.01 and the mass ratio of AEO-3 to PTFE is 0.0025, the dispersibility of the two dispersions is the most stable; this condition was used in the subsequent preparation process to prepare the composite membrane.
[0048] The key to enhancing the anti-fouling performance of the composite membrane is to adjust the surface energy to an appropriate range by controlling the proportion of PTFE. Figure 4 The figure shows the changes in the Zeta potential of PTFE-ZrO2 mixed solutions with different volume ratios at pH 9 and 11 after adding the optimized concentration of dispersant. Under pH 11 conditions, the Zeta potential value of each PTFE-ZrO2 dispersed mixed solution is about -45mV, and the absolute value of the Zeta potential is significantly higher than that under pH 9 conditions, indicating that under pH 11 conditions, after adding a certain amount of optimized dispersant, the PTFE-ZrO2 mixed solution is more stable.
[0049] Effect of sintering temperature on the surface morphology of composite films
[0050] Figure 5 The surface morphology of the composite membrane with a volume ratio of PTFE to ZrO2 of 1:3 at different sintering temperatures is shown. According to the TG-DSC curve, the PTFE particles begin to melt at about 320°C and decompose rapidly above 500°C, so the selected sintering temperatures are 320°C, 340°C and 360°C, respectively. The surface of the composite membrane is relatively complete after sintering at 320°C and 340°C. The membrane surface presents a slit-like pore structure, which is attributed to the irregular shape of the PTFE particles and the size difference between the two particles. As the temperature increases to 340°C, the slit-like pore structure becomes narrower due to the tighter connection between the particles. However, when the temperature is further increased to 360°C, the PTFE particles are in a molten state, resulting in a large number of irregular holes on the membrane surface. Figure 5 It further shows that the pure water permeability of the composite membrane sintered at 360℃ is significantly higher than that of the membrane sintered at 320℃ and 340℃. Figure 5 Figures e and f show that the dynamic contact angles of water and diiodomethane decrease faster. The permeability performance of the composite membranes sintered at 320℃ and 340℃ is not significantly different. The final sintering temperature is 340℃.
[0051] The effects of solid content and coating time on the integrity of the composite film were also investigated. The composite film obtained under the conditions of solid content of 0.9wt% and coating time of 30s showed better integrity and no obvious cracking. Figure 6 As shown in a, under the optimized preparation conditions, the surface of the composite membrane is intact and has no obvious defects. Figure 6 The uniform distribution of Zr and F elements on the membrane surface in b and c of 6 indicates that PTFE exists in the membrane layer, proving that the composite membrane was successfully prepared. This is further confirmed by the FTIR spectrum. Compared with the base membrane, the hybrid membrane has a -1 and 1150cm -1 Two new peaks appeared at , which were attributed to the -CF2- stretching vibration of PTFE molecules. Figure 6 The d shows that the surface roughness of the composite membrane is lower than that of the base membrane. Low surface roughness can reduce the adhesion and accumulation of microorganisms on the membrane surface, thereby enhancing the anti-fouling performance of the composite membrane. Figure 6 From the EDS line scan analysis of the composite film cross section, it can be seen that the thickness of the composite film is about 1.2μm. F and Zr elements are mainly concentrated in the composite film layer, and the signal value decreases with increasing depth. On the contrary, the signal value of the Al element increases with increasing depth. These results show that PTFE and ZrO2 particles are evenly distributed in the composite film layer, and there is a clear boundary between the composite film layer and the base film. Effect of PTFE doping amount on surface energy
[0052] The antifouling performance strongly depends on the surface characteristics of the composite membrane. By adjusting the PTFE content in the zirconia membrane, compact ultrafiltration (UF) membranes with different surface energies can be prepared. The surface energy of each membrane is determined by calculating the static contact angle, such as Figure 7 As shown in a. The increase in PTFE content leads to an increase in the contact angle of the composite membrane, while the surface energy decreases. As the PTFE content gradually increases, the surface energy of the membrane increases from 73.82 mJ·m -2 and 76.72 mJ·m -2 The lowest value was 17.94 mJ·m -2 .
[0053] The pure water permeability of the base film, ZrO2 film and composite film is as follows Figure 7 As shown in b. Due to the smaller pore size and lower surface energy of the composite membrane, its permeability is lower than that of the base membrane. In addition, as the PTFE content in the membrane increases, the permeability first increases and then decreases. This initial increase in permeability may be due to the increase in PTFE particles leading to an increase in the pore size of the composite membrane, while the subsequent decrease in permeability may be due to the further increase in PTFE content leading to a decrease in the hydrophilicity of the composite membrane.
[0054] The PTFE content in the hybrid membrane was further optimized by simulating fermentation broth filtration experiments. In the test, the temperature was maintained at 25°C and the membrane surface flow rate was 2 m·s -1 , the transmembrane pressure difference is 0.2MPa, the results are as follows Figure 8 The simulated fermentation broth caused the bottom membrane to be seriously contaminated, causing the flux to drop from 323.0 L·m in 15 minutes. -2 ·h -1 Rapidly dropped to only 66.4L·m -2 ·h -1 After 90 minutes of operation, the flux of the bottom membrane stabilized at about 21 L·m -2 ·h -1 In contrast, the flux of the ZrO2 membrane and the composite membrane also decreased, but to a lesser extent than that of the base membrane. After 90 minutes of testing, the ZrO2 membrane achieved a higher stable flux of about 31 L·m -2 ·h -1 Among all the hybrid membranes tested, the P1Z3 composite membrane performed best, with a maximum stable flux of 62.9 L·m -2 ·h -1 , while the stable flux of other composite membranes is mainly between 30-40 L·m -2 ·h -1 This is almost three times the stable flux of the bottom membrane and twice that of the ZrO2 membrane. Figure 8Figure b shows that most of the pollutants on the membrane surface can be removed by effective chemical cleaning. After pure water rinsing and chemical cleaning, the flux recovery rate (FRR) of the bottom membrane remained below 70%. All composite membranes exceeded 85%, among which the FRR of the P1Z3 composite membrane was as high as 96.9%. These results highlight the excellent anti-fouling performance of the composite membranes. Considering the pure water flux and the application results in simulated fermentation broth, the P1Z3 composite membrane performed best among all composite membranes.
[0055] The high stable flux and flux recovery rate (FRR) of the composite membrane can be attributed to two aspects. First, the -CF2- groups of the PTFE particles in the composite membrane provide low surface energy characteristics, which effectively weaken the interfacial bonding between the pollutants and the membrane surface. Under appropriate shear stress, the pollutants can be easily removed from the membrane surface. Although many studies have shown that in the surface energy range of 20-30mJ·m -2 Microbial attachment was minimal when the composite membrane was used, but these findings were mainly based on research on developing anti-fouling coating materials. In this study, the composite membrane had a rich pore structure. The presence of the porous structure and ZrO2 particles, as well as the difference in roughness, led to a decrease in the measured contact angle. Therefore, although the surface energy of the optimized composite membrane was higher than 20-30mJ·m -2 , but its high flux and FRR in the fermentation broth still highlight the effective resistance of the membrane surface to biological fouling. Secondly, the main part of the composite membrane is ZrO2 particles. The presence of ZrO2 particles gives the composite membrane the characteristics of small pores, which significantly reduces the pore blockage and fouling caused by small molecules in the fermentation broth.
[0056] Application of composite membrane in fermentation broth
[0057] The actual ethanol fermentation broth from Shougang Langze Technology Co., Ltd. was then tested. Under constant conditions (temperature: 25°C, cross flow velocity: 3.0 m·s -1 , transmembrane pressure: 0.2MPa) clarification experiments were carried out using bottom membrane, ZrO2 membrane and P1Z3 composite membrane, such as Fig.10 As shown in a. It can be observed that the flux of the composite membrane remained stable throughout the filtration process, while the bottom membrane and ZrO2 membrane reached stability after 5 minutes. This phenomenon may be attributed to the complex composition and diverse pollutants in the actual fermentation broth, which led to the rapid formation of a complete gel layer on the membrane surface. The ZrO2 nanocrystals in the composite membrane have the characteristics of resisting protein adsorption and preventing pore clogging. By adding PTFE to adjust the surface energy, this synergistic effect effectively alleviated microbial contamination. Therefore, the stable flux of the composite membrane in actual ethanol fermentation broth is nearly 2.1 times that of the bottom membrane and about 1.5 times that of the ZrO2 membrane. Fig.10 The pictures in a represent, from left to right, the original ethanol fermentation liquid, the permeate of the composite membrane, the permeate of the ZrO2 membrane, and the permeate of the bottom membrane.
[0058] After the three membranes were washed in sequence, the results were as follows: Fig.10 As shown in b. The results are similar to those obtained in the simulated fermentation broth. However, the degree of membrane fouling in the actual fermentation broth was significantly higher. In the simulated fermentation broth without protein, the flux recovery rates (FRR) of the base membrane, ZrO2 membrane and composite membrane after pure water rinsing were 35.6%, 52.3% and 69.7%, respectively. In the actual fermentation broth, these values dropped to only 11.2%, 26.0% and 31.8%, respectively. After chemical cleaning, the FRR of the base membrane, ZrO2 membrane and composite membrane were 41.1%, 78.8% and 95.5%, respectively. This further shows that the composite membrane developed in this study can effectively combine the functions of anti-protein pore blocking and surface energy regulation to reduce microbial adsorption, thereby showing excellent anti-fouling performance in actual ethanol fermentation broth.
Claims
1. A method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy, characterized in that: The steps include: Step 1, mixing PTFE emulsion and ZrO2 dispersion to obtain PTFE-ZrO2 dispersion; Step 2, coating the ceramic membrane tube with a PTFE-ZrO2 dispersion by dip coating; Step 3, drying and sintering to obtain the PTFE-ZrO2 composite membrane.
2. The method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to claim 1, characterized in that: The solid content of the ZrO2 dispersion is 1-5%, the solid content of the PTFE emulsion is 40-70%, and the volume ratio of the PTFE emulsion to the ZrO2 dispersion is 1:9-1:1, and preferably 1:2-1:
4.
3. The method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to claim 1, characterized in that: The pH value of PTFE emulsion and ZrO2 dispersion is 9-13.
4. The method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to claim 1, characterized in that: The PTFE emulsion and / or ZrO2 dispersion also contains a dispersant, which is selected from NH4PAA or AEO-3. When NH4PAA is used in the ZrO2 dispersion, and the mass ratio of NH4PAA to ZrO2 is 0.005-0.05, AEO-3 is used in the PTFE emulsion, and the mass ratio of AEO-3 to PTFE is 0.001-0.
005.
5. The method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to claim 1, characterized in that: The coating time of dip coating is 20-50s.
6. The method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to claim 1, characterized in that: The sintering temperature in step 3 is 300°C-350°C, preferably 335-345°C.
7. The PTFE-ZrO2 composite membrane prepared by the method for preparing a small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy according to any one of claims 1 to 6 is characterized in that: The surface roughness Ra of the composite film is 20-30nm, and the surface energy is 25-35mJ·m -2 , the composite film thickness is 1-2μm.
8. Use of the small-pore anti-pollution PTFE-ZrO2 composite membrane with low surface energy as claimed in claim 1 in filtration and clarification of fermentation broth.
9. The use according to claim 8, characterized in that: The clarification working conditions of the composite membrane are: a membrane surface flow rate of 0.5-5 m / s and a transmembrane pressure difference of 0.1-1 MPa.
Citation Information
Patent Citations
Method for hydrophilic modification of water treatment separation membrane
CN112263919A
Method for improving preparation of Zr-based MOF (Metal Organic Framework) membrane by using intermediate modification layer and forward osmosis application of Zr-based MOF membrane
CN114471200A
PTFE-ceramic slurry for high-frequency microwaves, sintered film of PTFE-ceramic slurry and preparation method and application of PTFE-ceramic slurry and sintered film
CN115594512A
Microwave sintering-based polytetrafluoroethylene / ceramic composite membrane as well as preparation method and application thereof
CN120361743A
Alumina composite separation membrane, and method for manufacturing the same
JP2011255303A